Islam, Poda Na Lima, and Its Actuality in Etymology and Philosophy Perspectives - Iskandarsyah Siregar (Lakhomi Journal Scientific Journal of Culture, 2023)
The foundational ethos of a nation-state is inextricably linked with long-standing cultural tenets, often encapsulated in a codified philosophy that predates the state's formal establishment. These traditional values serve as an authoritative framework for addressing complex societal issues. Specifically, in the Indonesian context, there is a discernible challenge characterized by a multifaceted set of issues and inherent complexities in devising effective solutions. It is posited that these dilemmas can be ameliorated by adhering to the country's ingrained philosophical and traditional mores. If such a philosophy is rooted in religious principles, it is only through the application of these religious teachings that the veracity of traditional customs can be affirmed. In this regard, Islam is particularly salient as a religion of 'rahmatan lil'alamin,' possessing a universal applicability that encompasses all facets of human existence. The impetus for this research lies in its potential to catalyze a reorientation of societal perspectives, specifically among the Batak tribe. The objective is to align communal practices, including architectural and infrastructural developments, with the precepts of the Poda Na Lima philosophy. This alignment will be achieved by first establishing the points of congruence between the Poda Na Lima philosophy and the tribe’s religious and ethnic identity as Muslims and Bataks, respectively. To achieve this, the study employs qualitative methodologies guided by critical discourse analysis. The results unequivocally indicate that the quintessential principles enshrined in the Poda Na Lima philosophy are not merely instructive but also possess significant intrinsic value. Moreover, the entirety of the Poda Na Lima's content is congruent with and complementary to, Islamic doctrine.